(untitled) (Journal of Computational Mathematics, 2021)
In the present paper, we study the restricted inexact Newton-type method for solving the generalized equation 0f(x)+F(x), where X and Y are Banach spaces, f:X→ Y is a Fréchet differentiable function and FX ightrightarrows Y is a set-valued mapping with closed graph. We establish the convergence criteria of the restricted inexact Newton-type method, which guarantees the existence of any sequence generated by this method and show this generated sequence is convergent linearly and quadratically according to the particular assumptions on the Fréchet derivative of f. Indeed, we obtain semilocal and local convergence results of restricted inexact Newton-type method for solving the above generalized equation when the Fréchet derivative of f is continuous and Lipschitz continuous as well as f+F is metrically regular. An application of this method to variational inequality is given. In addition, a numerical experiment is given which illustrates the theoretical result.